Study on Isomeric Impurities in Cefotiam Hydrochloride - Tian, Ye; Chong, Xiao-Meng; Liu, Ying; Han, Ying; Hu, Chang-Qin; Yao, Shang-chen; Xu, Ming-Zhe (Frontiers in Chemistry, 2021)
In this study, two isomeric impurities were identified in cefotiam hydrochloride injection preparation and were characterized. Column-switching HPLC-MS and NMR techniques were used to identify the impurity 1 as the Δ3(4) isomers of cefotiam. Using software-based calculations, it was predicted that neither of the isomeric impurities was embryotoxic. This study provides a reference for the production, storage, and quality control of cefotiam and related cephalosporin antibiotics.